Spectrophotometric determination and thermodynamic studies of the charge transfer complexes of azelastine-HCl - Nahla N. Salama; Sawsan A. Abdel-Razeq; Shimaa Abdel-Atty; Naglaa El-Kosy (Faculty of Pharmacy, Cairo University, 2011)
Three charge transfer complexes of azelastine as n-donor with π acceptors, dichloro-dicyanobenzoquinone (DDQ), chloranilic acid (CA) and tetracyanoquinodimethane (TCNQ) were prepared in acetonitrile. They yield a radical anions measured at 456, 520 and 841 nm within concentration ranges of 8.0-72, 40-320 and 1.6-14.4 μg mL−1 with good correlation coefficients (r = 0.9996-0.9998). The molar absorptivities and association constants for the colored products were evaluated using the Benesi-Hildebrand equation. The free energy change (ΔG0) and the enthalpy of formation (ΔH0) as well as the entropy (ΔS0) were determined for the reaction product with TCNQ. The methods were successfully applied to the analysis of azelastine in its pharmaceutical preparations, where no interferences could be observed from the additives commonly present in the eye drops or nasal spray as proved by good mean recoveries of 98.89 ± 1.06-99.54 ± 1.84%. The results were compared, favorably with the manufacturer method and validated according to ICH guidelines.